Trinuclear Sr[UO2L3]2(H2O)4 and pentanuclear Sr[UO2L3]42− uranyl monocarboxylate complexes (L-acetate or n-butyrate ion). Issue 4 (28th November 2014) - Savchenkov, Anton V.; Klepov, Vladislav V.; Vologzhanina, Anna V.; Serezhkina, Larisa B.; Pushkin, Denis V.; Serezhkin, Viktor N.
Abstract : The structures of three strontium(ii ) uranyl heterometallic tri- and penta-nuclear complexes with bridge acetate and butyrate ions are discussed. Abstract : Crystals of two acetate complexes, Cs2 Sr[UO2 L3 ]4 (1 ) and [Sr(H2 O)6 ][UO2 L3 ]2 Sr(H2 O)4 [UO2 L3 ]2 2 (2 ), and one n -butyrate complex, Sr(H2 O)4 [UO2 L3 ]2 ·2H2 O (3 ), of uranium(vi ), where L is a corresponding monocarboxylate ion, were studied by means of FTIR spectroscopy and single crystal X-ray analysis. The structure of1 contains pentanuclear anionic complexes, Sr[UO2 L3 ]4 2−, bonded in a three dimensional framework by electrostatic interactions with Cs + cations. The structure of2, in addition to 'typical' uranyl triacetate complexes of [UO2 L3 ] − and [Sr(H2 O)6 ] 2+ cations, contains neutral trinuclear complexes, Sr(H2 O)4 [UO2 L3 ]2 . The structure of3 with n -butyrate ions consists of neutral complexes of Sr(H2 O)4 [UO2 L3 ]2 and molecules of crystallized water. Analysis of intermolecular interactions in2 and3 by means of two independent approaches (molecular Voronoi–Dirichlet polyhedra and molecular Hirshfeld surfaces) revealed that discrete complex groups are connected with one another mostly due to H/O hydrogen bonds and H/H dispersion interactions. A dynamic balance among mono- and poly-nuclear complexes in aqueous solutions containing R 2+ and [UO2 L3 ] − ions is proposed. The effect of the alkyl chain and the nature of the R 2+ cation on the balance is discussed.